Synthesis of modified rice husk activated carbon and study on their carbon dioxide (co2) adsorption capacity - Siti Noraishah, Masoum Raman (2021)
Characterization studies of impregnated activated carbon with monoethanolamine (MEA), diethanolamine (DEA), and piperazine as potential carbon dioxide (CO2) adsorbent were conducted. The adsorption capacity of the activated carbon can be increased by introducing amine group on the surface of the adsorbent. MEA, DEA, and piperazine were selected as amino compounds for the binding process on activated carbon surface. The synthesis of impregnated activated carbon was prepared according to concentration and mixture ratio. The physicochemical properties of impregnated activated carbon were characterized by x-ray diffraction (XRD), Brunauer, Emmett and Teller (BET), fourier transform infrared spectroscopy (FTIR) and field emission scanning electron microscopy (FESEM). The XRD analysis was used to determine the type of compound present on the activated carbon surface. The result revealed that the diffraction angles around 21.54º to 22.18º were linked for pyrazole, ethanolamine, diethanolamine, and benzalazine which prove the presence of hydrocarbon and amine on the activated carbon surfaces. From the BET analysis, the total surface area and pore volume decreased with increase in concentration of alkanolamine. The presence of amide functional groups in FTIR analysis at 3288 cm-1and 1651 cm-1band for the impregnated activated carbon proved that a reaction occured between carboxyl groups on the activated carbon surfaces with amine bonded. As for FESEM analysis, it was shown that the morphology of the non-impregnated activated carbon contained many pores on its surface while the pores on the impregnated activated carbon with alkanolamine were filled with amines according to the selected concentration. The sample chosen for CO2 adsorption capacity study was of the highest concentration and mixture ratio of piperazine, namely 75 wt.% and 1:2 activated carbon to piperazine ratio, respectively. The CO2 adsorption capacity studies show that the best condition for adsorption process to take place was at bed temperature of 25°C and feed gas flow rate of 20 ml/min. The CO2 uptake was highest at this temperature and flow rate for piperazine impregnated activated carbon followed by the regenerated sample and non-impregnated activated carbon which were 145.42, 95.81, and 42.00 mg-CO2/g-adsorbent respectively. The regeneration recovery for the piperazine impregnated activated carbon was more than 65%.